Unsuccessful introductions of adult elephant bulls to confined areas in South Africa - Marion Garaï; Richard Carr (Pachyderm)
This study assessed the reasons why some mature elephant bull introductions to game-fenced properties have been unsuccessful. Between 1998-2000 71 adult bulls from Kruger NP were transferred to 15 properties. Break-outs, circumstances where bulls broke out of a functional electrified perimeter fence, or a release boma and a perimeter fence and did not return, occurred in 5 properties. Observations suggest the 8 bulls involved had not developed a respect for electric fencing, but this investigation was unable to identify particular common factors that may lead to break-outs. However, several factors appear to influence break-outs including: the construction and electrification components used in the release boma; the age, social staus and number of bulls introduced; the proximity to their previous range; and the presence of established founder family groups. These are discuss and related to specific break-outs, and recommendations associated with each are reviewed. Suggests the most important aspect to introducing and establishing elephants in a new environment and specifically into small, confined areas is the training period in the release boma, and if this involves initiation to electric fencing it is at this point a lasting respect must be developed.